2019
DOI: 10.1001/jamafacial.2019.0483
|View full text |Cite
|
Sign up to set email alerts
|

Categorization and Analysis of Nasal Base Shapes Using a Parametric Model

Abstract: IMPORTANCE Nasal base view is important for rhinoplasty analysis. Although some descriptors of nasal base shape exist, they are largely subjective and qualitative.OBJECTIVE To evaluate a parametric model of nasal base shape and compare it with categorization by surgeons to create an objective classification system for clinical evaluation and communication. DESIGN, SETTING, AND PARTICIPANTSRetrospective cohort review of deidentified photographs of 420 patients evaluated for possible facial plastic surgery at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Rhinoplasties are a heavily researched group of procedures that have been aided by computer-generated models for surgical planning. 12,39,[76][77][78] Some of these models simply validated approaches to well-known procedures. However, some animal models demonstrated that nonbiologic printed dorsal septal cartilage scaffolds remain intact without migration after several months.…”
Section: Rhinoplastymentioning
confidence: 99%
“…Rhinoplasties are a heavily researched group of procedures that have been aided by computer-generated models for surgical planning. 12,39,[76][77][78] Some of these models simply validated approaches to well-known procedures. However, some animal models demonstrated that nonbiologic printed dorsal septal cartilage scaffolds remain intact without migration after several months.…”
Section: Rhinoplastymentioning
confidence: 99%